Kedudukan Hukum Tugas Pembantuan Sebagai Instrumen Koordinasi Pemerintah Pusat Dan Daerah Dalam Sistem Otonomi - Ali Ramdhani, Fahmi; Herdiyansah, Peri; Hardianti Putri, Efsa; Ridwan, Rivia (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The implementation of regional autonomy in Indonesia faces complex challenges in creating effective coordination between central and regional governments. This study aims to analyze the legal position of co-administration as a coordination instrument in the regional autonomy system, evaluate the effectiveness of coordination mechanisms, and identify juridical and implementative constraints. The research method uses a qualitative approach with library research to examine the legal construction of co-administration based on Law Number 23 of 2014 concerning Regional Government and its implementing regulations. The results show that co-administration has a strategic position as a bridging mechanism in the regional autonomy system with hybrid characteristics between centralization and decentralization. The juridical construction of co-administration contains four constitutive elements: assignment of partial government affairs, implementation by regional government, not full delegation of authority, and accountability to the assigning party. The effectiveness of coordination through co-administration is hampered by unclear division of authority, normative conflicts between regulations, resource limitations, and vertical-horizontal coordination barriers. The study concludes that optimizing the coordination function of co-administration requires reconstruction of the legal framework through regulatory improvement, strengthening coordination capacity, developing integrated monitoring evaluation systems, and establishing special dispute resolution mechanisms to create sustainable coordination in Indonesia's regional autonomy system.